2017
DOI: 10.1088/1361-6463/aa9357
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrical stability of nitrate ligand-based hexaaqua complexes solution-processed ultrathin a-IGZO transistors

Abstract: We report solution-processed, amorphous indium-gallium-zinc-oxide-based (a-IGZO-based) thin-film transistors (TFTs). Our proposed solution-processed a-IGZO films, using a simple spin-coating method, were formed through nitrate ligand-based metal complexes, and they were annealed at low temperature (250 °C) to achieve high-quality oxide films and devices. We investigated solution-processed a-IGZO TFTs with various thicknesses, ranging from 4 to 16 nm. The 4 nm-thick TFT films had smooth morphology and high-dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…To validate the simulation results, we compared them to measurement of ref. . The experimental data were measured for a‐IGZO TFT with inverted‐staggered structure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To validate the simulation results, we compared them to measurement of ref. . The experimental data were measured for a‐IGZO TFT with inverted‐staggered structure.…”
Section: Resultsmentioning
confidence: 99%
“…The simulation of NBIS and PBS agreed very well with what have been reported for solution‐processed ultrathin a‐IGZO TFT in ref. in which it was found that the thinner 4 nm show high stability compared with thicker 16 nm TFT for PBS and NIBS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, solution process and magnetron sputtering have been commonly used to achieve low temperature prepared a-IGZO TFTs. However, a-IGZO prepared by the solution process shows disadvantages such as lots of film defects, large roughness, and poor uniformity of large areas—inducing low carrier mobility of a-IGZO TFTs (generally < 10 cm 2 V −1 s −1 ), which cannot satisfy the requirements of high-definition flexible display applications [13,14,15,16]. The studies also showed that most of the sputtered a-IGZO TFTs always need an annealing process to guarantee their high performance, since unannealed a-IGZO fabricated by magnetron sputtering still have many defects inside [17,18,19].…”
Section: Introductionmentioning
confidence: 99%